Saving Liberalism from Itself The Spirit of Political Participation - Stacey, Timothy (Bristol University Press, 2022)
EPDF and EPUB available Open Access under CC-BY-NC-ND license. In the wake of populism, Timothy Stacey's book critically reflects on what is missing from the liberal project with the aim of saving liberalism. It explains that populists have harnessed myth, ritual, magic and tradition to advance their ambitions, and why opponents need to embrace rather than eschew them. Via examples of liberally oriented activists in Vancouver, it presents an accessible theorisation of these quasi-religious concepts in secular life.